Identification of Hepatitis G Virus Particles in Human Serum by E2-Specific Monoclonal Antibodies Generated by DNA Immunization - Schmolke, Susanne (American Society for Microbiology, 1998)
In order to elucidate the structure and morphology of hepatitis G virus (HGV), a recently isolated flavivirus, we generated a panel of eight monoclonal antibodies (MAbs) against the putative second envelope protein (E2) following DNA immunization. The MAbs were shown to be specific for four different epitopes on recombinant E2. MAb Mc6 was the only antibody able to detect the linear epitope LTGGFYEPL. In addition, Mc6 was able to immunoprecipitate viral particles in human blood samples as detected by reverse transcription-PCR amplification of HGV RNA. This precipitation could be competed by addition of saturating amounts of the linear peptide or abolished by addition of Nonidet P-40. We conclude that, albeit lacking the N-terminal sequence of a functional core protein, HGV builds classical viral particles displaying E2 envelope protein on their outer surfaces.